Carboxymethyl cellulose nanofiber composite polyacrylate emulsion copolymerization slurry and preparation method thereof

By using carboxymethylcellulose nanofiber composite polyacrylate emulsion copolymer slurry, the problems of complex slurry adjustment, high sizing rate and environmental pollution during sizing of high-branch pure cotton yarns are solved, and the goal of improving sizing performance and environmentally friendly reduction of sizing rate is achieved.

CN119877279APending Publication Date: 2025-04-25QINGDAO UNIV
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202311377833.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-10-24
Publication Date
2025-04-25

AI Technical Summary

Technical Problem

When sizing high-branch pure cotton yarns, the slurry adjustment process is complicated, the slurry rate is relatively high, and a large amount of PVA slurry that is difficult to biodegrade is used, resulting in environmental pollution.

Method used

Carboxymethylcellulose nanofiber composite polyacrylate emulsion copolymerization slurry is used, which consists of polyacrylate emulsion copolymerization slurry and cellulose nanofiber aqueous dispersion. The mass amount of cellulose nanofiber accounts for 0.5%-2.5% of the dry weight mass of the polyacrylate emulsion copolymerization slurry.

Benefits of technology

The slurry is easy to biodegradate, simplifies the sizing process, reduces the sizing rate, and improves the comprehensive weaving performance of the slurry, avoiding environmental pollution.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
  • Figure SMS_2
    Figure SMS_2
Patent Text Reader

Abstract

The invention discloses a preparation method of a carboxymethyl cellulose nanofiber composite polyacrylate emulsion copolymerization slurry, which is characterized by comprising the following steps: adding a polyacrylate emulsion copolymerization slurry into a carboxymethyl cellulose nanofiber aqueous dispersion, fully and uniformly stirring to obtain a mixture, adding an initiator, and uniformly stirring to obtain the carboxymethyl cellulose nanofiber composite polyacrylate emulsion copolymerization slurry. And carrying out reduced pressure dehydration concentration on the obtained carboxymethyl cellulose nanofiber composite polyacrylate emulsion copolymerization slurry, so as to obtain the carboxymethyl cellulose nanofiber composite polyacrylate emulsion copolymerization slurry with the solid content of less than 30%. The solid content of the cellulose nanocrystal composite polyacrylate emulsion copolymerization slurry is less than or equal to 45%. When the carboxymethyl cellulose nanofiber composite polyacrylate emulsion copolymer slurry provided by the invention is used for sizing 60s and 80s high-count pure cotton yarns, the common defects in the prior art that the size mixing process is complicated, the sizing rate is high, and a large amount of PVA (Polyvinyl Alcohol) slurry which is difficult to biodegrade and pollutes the environment is used can be overcome.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to a textile pulp and a preparation method thereof, in particular to an eco-friendly carboxymethyl cellulose nanofiber composite polyacrylate emulsion copolymer pulp and a preparation method thereof. Background Art

[0002] As we all know, textile sizing agents are mainly divided into three categories: starch, polyvinyl alcohol (PVA) and polyacrylic acid. Among them, polyvinyl alcohol (PVA) is widely used as the main sizing agent for cotton, polyester-cotton, polyester-viscose, nylon and other yarns due to its excellent film-forming properties, adhesion and good compatibility with other sizing agents, and is considered to be an ideal sizing agent. However, with the strengthening of environmental protection awareness, developed countries, especially European countries, have banned the use of PVA as a textile sizing agent due to the shortcomings of PVA sizing agents being difficult to biodegrade and causing serious pollution to the environment. my country has also proposed the development goal of not using or using less PVA sizing agents in the sizing process.

[0003] In recent years, high-count and high-density pure cotton fabrics have been favored by more and more consumers due to their smooth and soft feel and noble and elegant appearance. The warp yarn used to weave high-count and high-density pure cotton fabrics has a relatively low linear density and relatively low tensile breaking strength, which makes it relatively difficult to size the yarn. In order to meet the weaving requirements, for yarn counts ≥ 60 s The textile industry currently uses a combination of polyvinyl alcohol (PVA) sizing, starch sizing and polyacrylic acid sizing to size high-count pure cotton yarn, and the sizing rate is usually ≥13%. As a result, the existing sizing process generally has the disadvantages of complex sizing process, high sizing rate, and large-scale use of PVA sizing that is difficult to biodegrade and causes environmental pollution. In order to avoid the pollution of the environment caused by PVA sizing, simplify the sizing process, and reduce the amount of sizing, it is urgent to develop a new type of textile sizing with excellent sizing performance, low sizing rate and easy treatment of desizing wastewater, so as to realize the development strategy of green energy conservation and emission reduction in my country's textile industry.

[0004] From the perspective of resin structure, polyacrylic acid size is classified into three structural types: pure acrylic acid, acrylic acid acetate and styrene acrylic acid. From the perspective of dosage form, polyacrylic acid size includes three dosage forms: aqueous solution type, water emulsion type and solid powder type. It is a polyacrylic acid textile size prepared by free radical or ionic polymerization of one or more mixed monomers composed of acrylic monomers such as acrylic acid or methacrylic acid, acrylate or methacrylate, acrylamide and acrylonitrile and vinyl monomers such as vinyl acetate and styrene. Due to the designability of its structure and performance, it can meet the sizing performance requirements of different yarns. At the same time, this type of size in the desizing wastewater is easy to flocculate, recycle and be biodegraded, so it is considered to be an eco-friendly textile size. Compared with PVA size and starch size, the production cost of this type of size is relatively high, so it is currently mainly used as an auxiliary size for sizing various types of yarns. However, if its sizing performance can be improved and its sizing cost can be reduced by reducing the sizing rate, this type of sizing agent is expected to be used as the main sizing agent in sizing high-count pure cotton yarn with relatively high sizing cost.

[0005] Nanocellulose is a nanoscale fiber or crystal extracted from natural cellulose. It has the advantages of being degradable, renewable, non-toxic and high-strength. It can be used to prepare various advanced functional materials with high added value. According to the different preparation methods and sources, nanocellulose can be divided into three categories: cellulose nanocrystals (CNC), cellulose nanofibers (CNF) and bacterial cellulose (BC). These three types of nanocellulose have certain differences in structure, performance and application. Among them, CNC is a nanorod-like material with natural chirality, mainly composed of crystalline regions and quasi-crystalline regions, with a diameter between 5-30nm, a length ranging from 100 nm to several microns, and an aspect ratio usually between 5-50. There is no bending, winding, bifurcation or mesh structure; CNF is mainly composed of crystalline regions, quasi-crystalline regions and amorphous regions, with a diameter of about 3-100nm, a length of up to hundreds of microns, and an aspect ratio generally greater than 10. There may be filaments, winding or mesh structures; BC is a natural nanostructured polymer material with biodegradability produced by bacteria. Existing studies have shown that the use of nanocellulose to modify polymer materials can significantly improve the mechanical properties of polymer materials. However, through literature search, so far, no research reports on the use of cellulose nanocrystals to modify polyacrylate emulsion copolymer slurry have been found. Summary of the invention

[0006] The purpose of the present invention is to provide a carboxymethyl cellulose nanofiber composite polyacrylate emulsion copolymerization slurry, and the carboxymethyl cellulose nanofiber composite polyacrylate emulsion copolymerization slurry provided by the present invention is used to s and 80 sSizing of high-count pure cotton yarn can overcome the shortcomings of the prior art, such as complex sizing process, high sizing rate, and large-scale use of PVA sizing agents that are difficult to biodegrade and cause environmental pollution.

[0007] A carboxymethyl cellulose nanofiber composite polyacrylate emulsion copolymer slurry, characterized in that the slurry is composed of polyacrylate emulsion copolymer slurry and cellulose nanofiber aqueous dispersion, wherein the mass amount of cellulose nanofiber accounts for 0.5%-2.5% of the dry weight of the polyacrylate emulsion copolymer slurry; the cellulose nanofiber is prepared by high-pressure homogenization of a carboxymethyl cellulose aqueous solution with a carboxymethyl substitution degree of 0.34-0.4, and the fiber length tested by atomic force microscopy is 500nm-900nm, and the height is 5nm-10nm; the polyacrylate emulsion copolymer slurry The solid content is 30%-50%. It is prepared by conventional emulsion copolymerization of a mixed monomer consisting of acrylic acid, acrylamide, butyl acrylate and methyl methacrylate using water as solvent, wherein the mass percentage of acrylic acid to the total mass of the mixed monomer is 2%-5%, the mass percentage of acrylamide to the total mass of the mixed monomer is 15%-25%, the mass percentage of butyl acrylate to the total mass of the mixed monomer is 20%-40%, the mass percentage of methyl methacrylate to the total mass of the mixed monomer is 20%-40%, and the mass percentage of each monomer in the mixed monomer is 100%.

[0008] A method for preparing a carboxymethyl cellulose nanofiber composite polyacrylate emulsion copolymer slurry is characterized by being implemented according to the following steps: adding polyacrylate emulsion copolymer slurry to a carboxymethyl cellulose nanofiber aqueous dispersion, and then fully stirring to obtain a carboxymethyl cellulose nanofiber composite polyacrylate emulsion copolymer slurry with a solid content of less than 30%, and decompressing and dehydrating the obtained carboxymethyl cellulose nanofiber composite polyacrylate emulsion copolymer slurry to obtain a cellulose nanocrystal composite polyacrylate emulsion copolymer slurry with a solid content of less than or equal to 45%.

[0009] The carboxymethyl cellulose nanofiber composite polyacrylate emulsion copolymer slurry provided by the present invention is easy to biodegrade and can overcome the current domestic and foreign textile enterprises in the 60 s and 80 s The environmental pollution problem caused by the large amount of PVA sizing agent used in the production process of high-count pure cotton yarn is solved. The sizing agent is simple to prepare. Under the premise of significantly reducing the sizing rate, the sizing agent is used to treat 60 s and 80 s The comprehensive weaving performance of high-count pure cotton yarn is significantly better than that of the combined sizing agents commonly used in the textile industry.

[0010] The embodiments of the present invention are further described below by way of examples.

[0011] Example 1: Preparation of carboxymethyl cellulose nanofiber composite polyacrylate emulsion copolymerization slurry A Weigh 40 grams of 1% carboxymethyl cellulose nanofiber aqueous dispersion, add 100 grams of polyacrylate emulsion copolymer slurry PA-1 with a solid content of 40% (prepared by conventional emulsion polymerization of a mixed monomer consisting of acrylic acid, acrylamide, butyl acrylate and methyl methacrylate in a mass ratio of 5:20:40:35), and stir at room temperature for 1 hour to obtain cellulose nanocrystal composite polyacrylate emulsion copolymer slurry A with a solid content of 28.86%. The slurry is dehydrated under reduced pressure, and after dehydrating 50.22 grams of water, cellulose nanocrystal composite polyacrylate emulsion copolymer slurry A with a solid content of 45% can be obtained, referred to as slurry A.

[0012] Example 2: Preparation of carboxymethyl cellulose nanofiber composite polyacrylate emulsion copolymerization slurry B Weigh 66.67 g of 1.5% carboxymethyl cellulose nanofiber aqueous dispersion, add 100 g of polyacrylate emulsion copolymer slurry PA-1 with a solid content of 40% (prepared by conventional emulsion polymerization of mixed monomers consisting of acrylic acid, acrylamide, butyl acrylate and methyl methacrylate in a mass ratio of 5:20:40:35), and stir at room temperature for 1 hour to obtain carboxymethyl cellulose nanofiber composite polyacrylate emulsion copolymer slurry B with a solid content of 24.6%. The slurry is dehydrated under reduced pressure, and after dehydrating 64.17 g of water, a carboxymethyl cellulose nanofiber composite polyacrylate emulsion copolymer slurry B with a solid content of 40% can be obtained, referred to as slurry B.

[0013] Example 3: Preparation of carboxymethyl cellulose nanofiber composite polyacrylate emulsion copolymerization slurry C Weigh 40 grams of 1.5% carboxymethyl cellulose nanofiber aqueous dispersion, add 100 grams of polyacrylate emulsion copolymer slurry PA-2 with a solid content of 40% (prepared by conventional emulsion polymerization of mixed monomers consisting of acrylic acid, acrylamide, butyl acrylate and methyl methacrylate in a mass ratio of 4:20:36:40), and stir at room temperature for 1 hour to obtain carboxymethyl cellulose nanofiber composite polyacrylate emulsion copolymer slurry C with a solid content of 29%. The slurry is dehydrated under reduced pressure, and after dehydrating 38.5 grams of water, a carboxymethyl cellulose nanofiber composite polyacrylate emulsion copolymer slurry C with a solid content of 40% can be obtained, referred to as slurry C.

[0014] Embodiment 4: Sizing experiment 1. Slurry preparation: (1) Preparation of sizing solution for actual factory sizing production: In a 2-liter beaker, add 577.8 grams of deionized water, then add 37.5 grams of PVA-1799, 5 grams of PVA-205, 50 grams of GM8-60 and 3 grams of wax flakes to prepare a sizing solution with a solid content of 13%. Start stirring and heat to 95°C. Continue stirring and keep warm for 1 hour before using for sizing. Define this sizing solution as sizing solution formula R.

[0015] (2) Preparation of carboxymethyl cellulose nanofiber composite polyacrylate emulsion copolymer slurry: In a 2-liter beaker, add 200 grams of carboxymethyl cellulose nanofiber composite polyacrylate emulsion copolymer slurry with a solid content of 40%, add 800 grams of deionized water, prepare a slurry with a solid content of 8%, start stirring, and heat to 95°C for sizing. Among them, the slurries prepared using slurry A, slurry B and slurry C are defined as slurry formula A, slurry formula B and slurry formula C, respectively. 2. Sizing process: The prepared sizing solution was used to size 60s and 80s pure cotton yarns respectively at 95°C with a sizing speed of 50 m / min and a sizing pressure of 15KN using a Y606S single yarn sizing machine.

[0016] 3. Sizing performance test According to GB / T3916-1997, the tensile breaking strength of textile single yarn, the tensile breaking strength (TS) and tensile breaking length (BL) of the sized yarn were tested, and the strengthening rate (TSR) and breaking reduction rate (BLR) of the sized yarn were calculated. According to FZ / T01058-1999, the abrasion resistance (ART) of the sized yarn was tested by the reciprocating roller method, and the abrasion increase rate (ARR) of the sized yarn was calculated. According to FZ / T01089-2000, the number of hairiness of the sized yarn was tested by the projection technology method, and the hairiness flatness rate (FDR) was calculated. According to GB / T9995-1997, the moisture regain (MRR) of the sized yarn was tested, and according to the literature (Yu Yongjun, Effect of sizing formula on loom efficiency and desizing rate of polyester-cotton varieties, Cotton Textile Technology, 2020, 48(08), 11-13), the sizing rate (SR) and desizing rate (DSR) of the sized yarn were tested.

[0017] 4. Sizing performance test results Table 1 60 s Cotton Sizing Performance

[0018] Table 2 80 s Cotton Sizing Performance

[0019] From the data in Table 1 and Table 2, it can be seen that the carboxymethyl cellulose nanofiber composite polyacrylate emulsion copolymerization slurry is used to s and 80 s For pure cotton yarn sizing, when the sizing rate is at least 3% lower than the industrial formula, the various properties of sizing formula A, sizing formula B and sizing formula C are better than those of industrial formula R. Among them, although sizing formula C has the lowest sizing rate, it has the best comprehensive sizing performance. The results show that using a single sizing formula C for sizing high-count pure cotton yarn can not only simplify the sizing operation and reduce the sizing rate, but also improve the sizing performance. Therefore, it can completely replace industrial formula R for 60 s and 80 s For use with pure cotton yarn sizing.

[0020] The above description is not a limitation of the present invention, and the present invention is not limited to the above examples. Any changes, additions or substitutions made by ordinary technicians in this technical field within the essential scope of the present invention should fall within the protection scope of the present invention.

Claims

1. A carboxymethyl cellulose nanofiber composite polyacrylate emulsion copolymer slurry, characterized in that The slurry is composed of polyacrylate emulsion copolymer slurry and cellulose nanofiber aqueous dispersion, wherein the mass amount of cellulose nanofiber accounts for 0.5%-2.5% of the dry weight of the polyacrylate emulsion copolymer slurry; the cellulose nanofiber is prepared by high-pressure homogenization of a carboxymethyl cellulose aqueous solution with a carboxymethyl substitution degree of 0.34-0.4, and the fiber length tested by atomic force microscopy is 500nm-900nm and the height is 5nm-10nm; the solid content of the polyacrylate emulsion copolymer slurry is 30%-50%, and it is The mixed monomer consisting of acrylic acid, acrylamide, butyl acrylate and methyl methacrylate is prepared by conventional emulsion copolymerization using water as solvent, wherein the mass percentage of acrylic acid to the total mass percentage of the mixed monomers is 2%-5%, the mass percentage of acrylamide to the total mass percentage of the mixed monomers is 15%-25%, the mass percentage of butyl acrylate to the total mass percentage of the mixed monomers is 20%-40%, the mass percentage of methyl methacrylate to the total mass percentage of the mixed monomers is 20%-40%, and the mass percentage of each monomer in the mixed monomers totals 100%.

2. The method for preparing the carboxymethyl cellulose nanofiber composite polyacrylate emulsion copolymerization slurry according to claim 1, characterized in that The following steps are implemented: adding polyacrylate emulsion copolymer slurry to the carboxymethyl cellulose nanofiber aqueous dispersion, and then stirring it thoroughly to obtain a carboxymethyl cellulose nanofiber composite polyacrylate emulsion copolymer slurry with a solid content of less than 30%, and decompressing and dehydrating the obtained carboxymethyl cellulose nanofiber composite polyacrylate emulsion copolymer slurry to obtain a cellulose nanocrystal composite polyacrylate emulsion copolymer slurry with a solid content of less than or equal to 45%.